Subsequent injuries are more common than injury recurrences: An analysis of 1 season of prospectively collected injuries in professional Australian Football - Finch, C. F.; Cook, J.; Kunstler, B. E.; Akram, M.; Orchard, J. (The American Journal of Sports Medicine, 2017)
Background: It is known that some people can, and do, sustain >1 injury over a playing season. However, there is currently little high-quality epidemiological evidence about the risk of, and relationships between, multiple and subsequent injuries. Purpose: To describe the subsequent injuries sustained by Australian Football League (AFL) players over 1 season, including their most common injury diagnoses. Study Design: Cohort study; Level of evidence, 3. Methods: Within-player linked injury data on all date-ordered match-loss injuries sustained by AFL players during 1 full season were obtained. The total number of injuries per player was determined, and in those with >1 injury, the Subsequent Injury Classification (SIC) model was used to code all subsequent injuries based on their Orchard Sports Injury Classification System (OSICS) codes and the dates of injury. Results: There were 860 newly recorded injuries in 543 players; 247 players (45.5%) sustained =1 subsequent injuries after an earlier injury, with 317 subsequent injuries (36.9% of all injuries) recorded overall. A subsequent injury generally occurred to a different body region and was therefore superficially unrelated to an index injury. However, 32.2% of all subsequent injuries were related to a previous injury in the same season. Hamstring injuries were the most common subsequent injury. The mean time between injuries decreased with an increasing number of subsequent injuries. Conclusion: When relationships between injuries are taken into account, there is a high level of subsequent (and multiple) injuries leading to missed games in an elite athlete group.